Galiza no porto: evocação da semana cultural galega de 1935 - Soeiro, Teresa (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2017)
Revisiting the Galician Cultural Week, an event that took place in 1935. It assembled the elite of researchers who were members of the Galician Studies Seminary and the University of Santiago of Compostela together with their peers from Oporto University and other cultural institutions of Entre-Douro-e-Minho. They all were committed to the joint production of multidisciplinary knowledge about the Northwest lands, to studying its physiography, and to the interpretation of their shared past, while engaging as well in the debate on the scientific and technical innovations that were mobilizing intents and promised a better life for the future within the framework of the Galician nationalism and the longed for solidary fraternity with the North of Portugal. The intellectual convergences and individual friendships consolidated this cooperation that was kept alive throughout the hard times of the Spanish civil war up to now and shaped a valuable legacy for the subsequent generations.